Pediatric Uveitis - Ilknur Tugal-Tutkun (Journal of Ophthalmic & Vision Research, 2011)
Uveitis is less common in children than in adults, and its diagnosis and management can be particularly challenging. Young children are often asymptomatic either because of inability to express complaints or because of the truly asymptomatic nature of their disease. Even in advanced cases, parents may not be aware of severe visual impairment until the development of externally visible changes such as band keratopathy, strabismus, or leukocoria. Therefore, the diagnosis is often delayed and severe complications may be seen at the time of initial visit. Young children may not be cooperative for a complete ocular examination and subtle findings of intraocular inflammation such as trace cells may be easily missed in the early stages of the disease. Children, in general, tend to have more severe and chronic intraocular inflammation that frequently results in ocular complications and visual loss. In children who present with amblyopia or strabismus, a careful examination is required to rule out uveitis as an underlying cause. Delayed and variable presentations cause a distinct challenge in the diagnosis of uveitis in children, furthermore differential diagnosis also requires awareness of etiologies which are different from adults. There are unique forms of uveitis and masquerade syndromes in this age group, while some entities commonly encountered in adults are rare in children.